A hundred years after Fabla salvaje: the fantastic, mirrors and fear - García, Mara L. (2023)
The year 2023 is ecumenical because it is the hundredth anniversary of the publication of Escalas and Fabla salvaje. In this second novel, Vallejo uses the fantastic, mirrors and fear to materialise the concerns and obsessions of the male subjects, causing chaos in their lives. In contrast, the role of the woman in this work is relevant because she opens the portal to the unknown and is the instrument for the unacceptable to occur. In this short novel, the author of Trilce uses the fantastic to highlight the moral values of Andean women. The irruption of the unbelievable not only causes horror and disquiet in the receiver and the characters, but also destroys the male who questions the honour of the peasant woman. For the purposes of this analysis, we will use some critical studies by Todorov, David Roas, Pampa Arán, among others, as they are relevant to this research.